2011
DOI: 10.1016/j.actatropica.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of PfCRT 76T in two Malian villages and its prevalence in severe relative to non-severe malaria

Abstract: We investigated PfCRT 76T mutation in severe and non-severe malaria in Southern Mali. One hundred and ninety three severe malaria cases were each matched against two non-severe malaria cases. Patients with G6PD deficiency and any known hemoglobin abnormality were excluded. PfCRT 76T was present in 60.8% (n = 386) non-severe malaria cases and in 77.2% (n = 193) severe malaria cases (p <0.0001). In children 5 years or younger, these proportions were 62.9% (n = 294) vs. 73.5% (n = 147), respectively (p < 0.01). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Low levels of resistance have also been reported in Myanmar, South Korea, Vietnam, India, Turkey, Ethiopia, and in regions of Southern Africa and South America [ 3 , 8 , 9 ]. The occurrence of severe vivax malaria and patient’s deaths has been reported in Brazil [ 10 - 12 ] raising the possibility of an association between malaria severity and drug resistance [ 13 ]. In areas of CQ resistance, treatment of uncomplicated P. falciparum malaria is carried out with artemisinin-based combination therapy (ACT) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of resistance have also been reported in Myanmar, South Korea, Vietnam, India, Turkey, Ethiopia, and in regions of Southern Africa and South America [ 3 , 8 , 9 ]. The occurrence of severe vivax malaria and patient’s deaths has been reported in Brazil [ 10 - 12 ] raising the possibility of an association between malaria severity and drug resistance [ 13 ]. In areas of CQ resistance, treatment of uncomplicated P. falciparum malaria is carried out with artemisinin-based combination therapy (ACT) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, gene mutations incriminated in CQ and antifolate drug resistance had no association with complicated malaria [208] . In contrast, there was significant association of Pfcrt (codon 76) mutation and malaria severity in both groups of patients (children 5 years or younger and above 5 years) [209] .…”
Section: Virulence Pathogenesis and Clinical Manifestantionsmentioning
confidence: 59%
“…The association between the pfcrt 76T mutation and the host's age is controversial, where some studies have showed a signi cant association (May and Meyer 2003;Happi et al 2006 As regards a link with parasite density, the current study found that the percentages of the pfcrt 74I and 75E mutations and the CVIET mutant haplotype were signi cantly high in isolates from patients with a low parasitaemia level. Although the reason for these associations is unclear, previous studies reported signi cant associations of pfcrt mutations (particularly 76T) with parasitaemia and severity of infection (Al-Mekhla et al 2011;Wélé et al 2011;Atroosh et al 2012;Acharya et al 2018;Cuu et al 2020). However, another study found no signi cant association (Mayengue et al 2007;Atroosh et al 2016).…”
Section: Discussionmentioning
confidence: 98%